PENGENALAN SENAM KESEGARAN JASMANI PADA MASAYARAK DUSUN 1 DESA LORU KECAMATAN BIROMARU KABUPATEN SIGI - niswa salamung; helmi Rumbo; Noviany Banne Rasiman (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Gymnastics is a physical activity or body exercise that is chosen and created with a plan, arranged systematically according to the order of motion with the aim of forming a series of artistic movements that are interesting and develop a person in harmony. However, when in a wider environment, many people do SKJ exercises, or other exercises including meditation to calm themselves down. This activity of introducing healthy, cheerful, healthy exercise is a very useful activity where to introduce to residents what physical fitness is, what is healthy cheerful exercise and others. This activity is carried out as an effort to refresh physically and mentally as well as to unite the strength and intimacy of residents in the Dusun I environment, Loru Village, Biromaru District, Sigi Regency. The exercise was led directly by several gymnastics instructors so that participants could immediately see and follow the exercise or movement directly. The SKJ Gymnastics PKM activity was attended by 28 participants consisting of residents of Dusun I, Loru Village..